Adsorptive removal of methylene blue by chemically treated cellulosic waste banana (Musa sapientum) peels. Issue 6 (2nd November 2018) - Jawad, Ali H.; Rashid, Ramlah Abd; Ishak, Mohd Azlan Mohd; Ismail, Khudzir
ABSTRACT: Acid-treated banana peel (ATBP) was developed by H2 SO4 activation to be a potential adsorbent for methylene blue (MB) from aqueous solution. Batch mode adsorption studies were conducted by varying adsorbent dosage (0.02–0.30 g), solution pH (3–12), initial MB concentrations (10–300 mg/L) and contact time (0–1440 min). The adsorption data of MB by ATBP were in agreement with Langmuir isotherm, with maximum adsorption capacities of 250 mg/g at 303 K. The pseudo-first-order kinetic model best described the kinetic data. The adsorption of MB onto ATBP surface was endothermic in nature and spontaneous under the experimented conditions. Results supported the potential use of the ATBP as an effective adsorbent for the treatment of cationic dyes such as MB from aqueous solution.